MRI‐based abnormalities in young adults at risk of adverse bone health due to childhood‐onset metabolic & endocrine conditions. (12th December 2013) - McComb, C.; Harpur, A.; Yacoubian, C.; Leddy, C.; Anderson, G.; Shepherd, S.; Perry, C.; Shaikh, M. G.; Foster, J.; Ahmed, S. F.
Summary Objective Traditional methods of bone densitometry may not provide a comprehensive assessment of bone health. We aimed to assess bone micro‐architecture and bone marrow adiposity (BMA) by MRI in adults with osteogenesis imperfecta (OI) and endocrinopathy including GH deficiency and/or hypogonadism. Measurements High‐resolution micro‐MRI images were acquired at the tibia using 3T MRI to calculate parameters of bone micro‐architecture in seven adults with OI and 10 adults with endocrinopathies. MR Spectroscopy was performed in participants to calculate vertebral BMA, which was expressed as percentage fat fraction (%FF). Lumbar spine DXA was performed to assess bone mineral density. The MRI data were compared with a group of 22 healthy adults who were divided into two age‐matched control groups. Results Intra‐operator repeatability was high, with an average CoV of 1% for micro‐MRI and 2·5% for MRS. The ratio of apparent bone volume to total volume (appBV/TV) in the endocrinopathy and OI groups was lower than in age‐matched control groups (P = 0·003 and P = 0·008 respectively). A weak association between DXA BMD and appBV/TV was also observed (r = 0·5, P = 0·045). %FF was higher in the endocrinopathy group than in the age‐matched control group (P = 0·005), but no difference in %FF was observed between the OI group and their age‐matched control group (P = 0·26). Conclusions MRI provides valuable detailed information on the micro‐architecture and adiposity of bones and is capable of showing clear differences in bone parameters in a range of clinical conditions associated with abnormal bone health.